Avaliação do desempenho térmico de habitações sociais de Passo Fundo, RS - Menezes, Milton Serpa (2006)
This work evaluates the thermal performance of social housing, having as case study the implanted housing projects in Passo Fundo, RS, in the period from 2000 to 2004, aiming at verifying the applicability of the procedures of the regulations which are in force, especially NBR-15220 (ABNT, 2005). The adopted methodology is based on other already developed studies, the cited regulation and the project of regulation 02:136.01 (ABNT, 2004), relative to the thermal performance of constructions. In a sample of five representative home units of the municipal housing program of the PSH (Program of Subsidies to the Housing of Social Interest) type, there have been measurements of temperature of dry bulb air and relative air humidity in the winter in the year 2005 and in the summer of 2006. At the same time, there were calculations of evaluation parameters such as thermal transmittance of the walls and covering, thermal capacity, thermal delay and solar factor. The used software was EnergyPlus, developed for the evaluation of thermal and energy performance of buildings for analysis of the behavior of the buildings. The results of the inter-relationships between the constructive characteristics of the homes, the climatic parameters of the city and the temperature inside environments show that they partly meet the requirements of the regulations concerning the thermal performance, but that some parameters are below the established ones, demanding recommendations regarding typology, solar orientation, constructive and material technologies of the homes of social interest. It offers a diagnosis of the reality that will serve as subsidy for other studies about alternatives to meet the regulations related to the thermal performance of the housing programs of social interest in the Passo Fundo town and in the region